1999
DOI: 10.1046/j.1439-0450.1999.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Viral Antibodies in Llamas (Lama glama) in Argentina

Abstract: This study analysed sera from 390 llamas (Lama glama) from nine farms located in three different Argentine provinces: Buenos Aires, Cordoba and Jujuy. The samples were tested for antibodies against 8 virus known to infect cattle: bovine herpesvirus type 1 (BHV-1), bovine viral diarrhea virus (BVDV), bovine adenovirus (BAdV III), bovine enterovirus (BEV), bovine rotavirus (BRV), bluetongue virus (BTV), bovine leukaemia virus (BLV), and foot-and-mouth virus (FMDV) by conventional methods such as seroneutralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
44
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 8 publications
7
44
1
5
Order By: Relevance
“…In a serological survey conducted in Peru, involving 117 alpacas that grazed with cattle and sheep, the prevalence of antibodies to BVDV was 11% (Rivera et al, 1987) and Picton (1993) reported a prevalence of 4.4% in 270 llamas from Oregon in the USA. A study by Puntel et al (1999) found 2.05% (8/390) reactors to the BVDV in Science Publications AJV llamas, from nine farms located in three different provinces in Argentina.…”
Section: Clinical Signs and Pathologymentioning
confidence: 99%
“…In a serological survey conducted in Peru, involving 117 alpacas that grazed with cattle and sheep, the prevalence of antibodies to BVDV was 11% (Rivera et al, 1987) and Picton (1993) reported a prevalence of 4.4% in 270 llamas from Oregon in the USA. A study by Puntel et al (1999) found 2.05% (8/390) reactors to the BVDV in Science Publications AJV llamas, from nine farms located in three different provinces in Argentina.…”
Section: Clinical Signs and Pathologymentioning
confidence: 99%
“…Mehrota 1973'te (18) mandalarda enterovirusun izolasyon ve karakterizasyonunu yapmış-tır. Enfeksiyonun varlığı serolojik olarak da birçok ülke-de bildirilmiştir (4,22,23).…”
Section: Tartışma Ve Sonuçunclassified
“…Nötralizan antikorlar insan, maymun, lama, kö-pek, koyun, keçi, sığır, tavşan ve kanatlılarda tespit edilmiş (17,21,22,27) olmasına rağmen, Tip 2 sadece evcil sığırlardan izole edilmiştir (4,21,25,29).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Llama and camel are relatively healthy, although they can be infected with many pathogens [3,7,12,13,15,17], which infect cattle, sheep and horse. However, the roles of inflammatory cytokines such as IL-1, IL-6 and TNFα in bacterial infections are not well understood in Camelidae.…”
mentioning
confidence: 99%